Consideration of the Upper Error Bound of Measurement Complex in the Analysis of Digitized Signals - Zubko, A. V.; Shcheka, V. I. (Science and Transport Progress, 2025)
Purpose. This work aims to: enhancing the reliability of certification tests for new rolling stock by integrating measurement system error considerations into the data analysis process; ensuring a more precise evaluation of compliance with safety and performance standards, minimizing the risk of undetected defects that could emerge during operation; improving risk assessment by reducing measurement uncertainties, thereby strengthening the decision-making process for rolling stock approval. Methodology. Analyzing existing approaches to certifying new rolling stock in accounting for measurement system errors. Developing a method for systematically integrating these errors into the data analysis process to enhance result accuracy. Assessing the impact of this approach on certification reliability and its effectiveness in identifying potential operational risks before deployment. Findings. An improved certification process incorporating measurement system error considerations has been proposed. The study demonstrates that this approach significantly reduces the probability of overlooking defects that may only become apparent during operation, thereby increasing the overall reliability of certification tests. Originality. A method for assessing the reliability of certification test data while considering measurement system errors has been developed. It has been proven that integrating these data into the test analysis process improves the accuracy of predicting the operational reliability of rolling stock and enhances the overall effectiveness of certification procedures. Practical value. The proposed approach enhances railway transport safety by ensuring a more reliable and accurate certification process for new rolling stock. This is particularly relevant in the context of Ukraine’s railway fleet modernization, including the introduction of Hyundai Rotem and Tarpan electric trains, as well as Škoda locomotives. By refining certification procedures, this methodology contributes to safer and more efficient railway operations.